Hubungan Ekstensibilitas Hamstring dan Stabilisasi HIP pada Pemain Futsal Pematangsiantar - Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Gea, Yosni Handayani (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2025)
Objective: To find out the correlation between hamstring extensibility and hip stability in the futsal players.Method: This study is a non-experimental research in the form of correlation studies to analyze the relationship between variables. A total sample of 20 futsal players from the Faculty of Physiotherapy at Esa Unggul University 2016-2018 aged 19-22 years. Measuring instruments used are sit and reach test for hamstring extensibility and single leg stance test for hip stability. Results: The results of measurements of sit and reach test were 25.45 ± 7.04 and in the single leg stance test the dominant side was 38.22 ± 19.76, the non-dominant side was 40.65 ± 18.19. Correlation test with the Spearman Rank Test obtained r= -0,483 for hamstring extensibility and dominant side hip stability, and r=-0,166 for the non-dominant side. Conclusion: There is no correlation between hamstring extensibility and hip stability in futsal players.